Availability and accuracy of occupation in cancer registry data among Florida firefighters. - Laura A McClure; Tulay Koru-Sengul; Monique N Hernandez; Jill A Mackinnon; Natasha Schaefer Solle; Alberto J Caban-Martinez; David J Lee; David J Lee; Erin Kobetz (PLoS ONE, 2019)
Objectives Occupational exposures significantly contribute to the risk of adverse cancer outcomes, and firefighters face many carcinogenic exposures. Occupational research using cancer registry data, however, is limited by missing and inaccurate occupation-related fields. The objective of this study is to determine the frequency and predictors of missing and inaccurate occupation data for a cohort of career firefighters in a state cancer registry. Methods We conducted a linkage between data from the Florida Cancer Data System (1981-2014) and the Florida State Fire Marshal's Office (1972-2012). The percentage and the odds of having a firefighting-related occupation code in the cancer record were calculated, adjusting for other occupation and cancer-related factors. Results Among 3,928 career firefighters, nearly half (47%) were missing a registry-dervived occupation code and only 17% had a firefighting-related code. Males were more likely to have a firefighting-related code (OR = 2.31;95%CI: 1.41-3.76), as were those with more recent diagnoses (OR1992-2002 = 2.98;95%CI: 1.57-5.67; OR2003-2014 = 11.40;95%CI: 6.17-21.03), and those of younger ages (OR45-64y = 1.26;95%CI: 1.03-1.54; OR20-44y = 2.26;95%CI: 1.73-2.95). Conclusions Accurate occupation data is key for identifying increased risk of advserse cancer outcomes. Cancer registry occupation fields, however, are overwhelmingly missing for firefighters and are missing disproportionally by sociodemographic and diagnosis characteristics. This study highlights the lack of accurate occupation data available for hypothesis-driven cancer research. Cancer registry linkage with external occupational data sources represents an essential resource for conducting studies among at-risk populations such as firefighters.